A Survey of the Experiences of Paraprofessionals With Roles, Training, and Communication When Working With Students With Autism. (June 2022) - Morin, Kristi L.; Nowell, Sallie; Steinbrenner, Jessica; Sam, Ann; Waters, Victoria; Odom, Samuel L.
Paraprofessionals are critical members of instructional teams for students with autism; however, little is known about their job preparation and professional development needs. This study addressed the gap in the literature by surveying 325 paraprofessionals in public school settings in the United States and Guam who reported working with students with autism. Data were gathered on paraprofessionals' (a) roles and responsibilities, (b) applied knowledge from different types of professional development, (c) perceived barriers to professional development, and (d) types and timing of communication with their supervising teachers. The results of this study have direct implications for individuals interested in developing a model of professional development that will meet the unique needs of paraprofessionals who work with students with autism.